TT 126: In Search of a “Lost” Tomb - Kaczanowicz, Marta.
The location of Theban Tomb no. 126, a small Late Period tomb belonging to the scribe and army commander Hormes, has long been a puzzle to scholars. The tomb was visited and recorded in the first half of the nineteenth century by the joint Franco-Tuscan expedition. It was allocated the number 23 and a short description in the diaries of Champollion and Rosellini. The tomb later appeared on the list of Theban Tombs as TT 126. However, Porter and Moss, Topographical Bibliography of Ancient Egyptian Hieroglyphic Texts, Reliefs, and Paintings presents conflicting information on the location of the tomb, and today its exact position is uncertain, as several places have been suggested over the years. In this paper we propose an alternative hypothesis, according to which the answer to the question of the correct location of TT 126 had in fact been identified long ago.